Coxsackievirus B3 Directly Induced Th17 Cell Differentiation by Inhibiting Nup98 Expression in Patients with Acute Viral Myocarditis - Long, Qi; Liao, Yu-Hua; Xie, Yu; Liang, Wei; Cheng, Xiang; Yuan, Jing; Yu, Miao (Frontiers in Cellular and Infection Microbiology, 2016)
Th17 cells play a key role in the progression of coxsackievirus B3 (CVB3)-induced acute viral myocarditis (AVMC). However, the direct effect of virus on Th17 cell differentiation is still unknown. Recently, nucleoporin (Nup) 98 has been proved to be associated with lymphocyte differentiation. Therefore, we investigated whether Nup98 mediated Th17 cell differentiation in AVMC. In our study, patients with AVMC and healthy controls were recruited. The results showed that CVB3 could enter into the CD4+ T cells in AVMC patients and healthy controls. After transfecting purified CD4+ T cells with CVB3 in vitro, the Th17 cell frequency, IL-17 secretion, and RORγT synthesis were increased while the Nup98 levels were decreased. Furthermore, down-regulating Nup98 expression by siRNA-Nup98 in CD4+ T cells resulted in the elevated Th17 cell frequency and IL-17 secretion, along with enhanced levels of RORγT, dissociative p300/CBP, and acetylated Stat3. Up-regulation of Nup98 expression by pcDNA3.1-Nup98 showed the opposite effects. Our results suggested that CVB3 directly induced CD4+ T cell differentiation into Th17 cells by inhibiting Nup98 expression, representing a therapeutic target in AVMC.